Aproximaciones a la didáctica del patrimonio cultural y a la educación artística en la educación infantil - Piña, Olga Duarte (2019)
This paper reflects on the possible relationships between artistic and heritage education, taking the values that both fields of knowledge can provide to children in pre-school education. It is also defended that it is necessary to start in the first stage of schooling with artistic and patrimonial training when the organization of the curriculum is not conditioned by the disciplinary organization and where the spaces and school times are flexible. And above all to take advantage of the innate characteristics of human beings unconditioned in early childhood: curiosity, imagination and creativity. To support this theoretical approach, the design of a didactic proposal for the educational stage of 3 to 6 years is developed